Status brazdarja (Rhysodes sulcatus) v Sloveniji (Coleoptera: Rhysodidae): dosedanje poznavanje in raziskovalne perspektive - Vrezec, Al (Acta entomologica slovenica (Ljubljana), 2007)
As a virgin forest species and a species of conservation importance, Rhysodes sulcatus is nowadays more studied beetle species in Slovenia, especially in the scope of Natura 2000 project. It was discovered first in a virgin forest reserve Rajhenavski Rog in the alpine biogeographical region, but on 27. 5. 2006 it was also found in the Regional Park Boč (NE Slovenia) in the continental region. The beetle was found on a dead rotten trunk of Beech (Fagus sylvatica) in a forest fragment of Chestnut and Beech (Castaneo-Fagetum) at elevation 675 m a. The area 1 km around is covered mainly by Beech forest (77%), the rest by meadows, pastureland, settlements and other non-forest habitat types. This finding of otherwise poorly known species in Slovenia indicates that further studies of the species should be oriented not only to virgin forest reserves, but also to managed forests wherethe virgin forest structure is still preserved with a sufficient amount of dead wood available.
Keywords: brazdarji; entomologija; favna; Slovenia; Slovenija